Comparison of Visual Performance and Patient Satisfaction Outcomes with Two Trifocal IOLs with Similar Optical Design but Different Materials - Poyales F (Dove Medical Press, 2020)
Francisco Poyales,1 Ricardo Pérez,1 Israel López-Brea,1 Ying Zhou,1 Laura Rico,1 Nuria Garzón1,2 1Miranza IOA, Madrid, Spain; 2Optometry and Vision Department, Universidad Complutense, Madrid, SpainCorrespondence: Nuria GarzónMiranza IOA, C/Galileo 104, Madrid 28003, SpainTel +34 915353570Email nuria.garzon@miranza.esPurpose: To compare clinical outcomes in a prospective trial of cataract surgery patients bilaterally implanted with two different trifocal intraocular lenses (IOLs) with very similar optical designs but consisting of different IOL materials (hydrophobic and hydrophilic).Patients and Methods: Fifty-one patients (102 eyes) were randomized to receive trifocal IOLs bilaterally – FineVision POD F (hydrophilic) or FineVision POD F GF (hydrophobic) (both PhysIOL, Liége, Belgium). The follow-up period was 3 months. Outcome measurements included uncorrected distance (UDVA), corrected distance (CDVA), distance-corrected intermediate (DCIVA), and distance-corrected near visual acuity (DCNVA), refraction, negative dysphotopsia, optical quality of vision, contrast sensitivity under photopic and mesopic conditions, halometry (discrimination index), and patient-reported outcomes.Results: At the final study visit, mean (SD) values for binocular UDVA, CDVA, DCIVA (80 cm), and DCNVA (40 cm) were − 0.01 (0.06), − 0.04 (0.04), 0.09 (0.10), and 0.10 (0.09) logMAR, respectively, for POD F, and 0.01 (0.08), − 0.03 (0.03), 0.08 (0.1), and 0.13 (0.11) respectively, for POD F GF. Defocus assessments showed a continuous curve with a functional range of visual acuity (≤ 0.15 logMAR) from ∼ 30 cm to infinity in both groups. The discrimination index was > 0.85 for all patients, and both groups showed similar contrast sensitivity under photopic and mesopic conditions. At 3 months, no patient reported negative dysphotopsia, and high satisfaction rates were observed.Conclusion: Clinical outcomes showed no significant difference between each lens when measured at 1 month and 3 months after implantation. This equally good clinical performance of hydrophilic and hydrophobic trifocal lenses allows the surgeon to choose the IOL material based on personal preferences or patients’ needs.Keywords: trifocal FineVision, intraocular lens, biomaterial, hydrophobic, hydrophilic, glistening-free